MEDIA SOCIALIZATION OF INDIVIDUALS IN MODERN INFORMATIONAL SOCIETY - Serhii Savchenko; Vitali Kurilo (National Academy of Educational Sciences of Ukraine, 2018)
The article deals with the analysis of the essential characteristics of media socialization of individuals in the informational society. Based on the theoretical analysis held, the author arrives at the conclusion that media socialization is a topical aspect of the social development of individuals in the social and cultural space of the informational society and is an important component of the modern process of individuals' socialization. In conditions of modern challenges there increases scholars' attention to the problems of youths' socialization - young men being at the stage of the development of their personalities as future professional, they being engaged in the virtual reality of the modern social and cultural space. In this context, it is hard to overestimate the role of institutions of higher education as the leading agents of a socially controlled socialization of individuals in modern social and cultural environment.